The Effectiveness of Using Google Classroom for Self-Directed Learning (SDL) Students in Learning English - Siahaan, Basar Lolo (Universitas Pahlawan Tuanku Tambusai, 2022)
This course aims to explore the use of Google Classroom to improve student learning (SDL) learning English. Using comprehensive research, 50 English Language Education students at HKBP Nommensen Pematangsiantar University were tested before being offered English language support supported by the use of Google Classroom for one semester. After the treatment, the students took a test after using the PRO-SDLS instrument to see if there was a statistical difference between the results of the pre-test and post-test. The results showed that there was a significant difference in SDL students between the beginning of the test and the post-test. Therefore, it can be concluded that the use of Google Classroom can help students develop their SDL skills in learning English